2018
DOI: 10.1080/14786419.2018.1457664
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and in vitro antibacterial and antiproliferative activities of the essential oil from the leaves of Psidium myrtoides O. Berg (Myrtaceae)

Abstract: In this study, the chemical composition and antibacterial and antiproliferative potential of the essential oil obtained from fresh leaves of Psidium myrtoides (PM-EO) against oral pathogens and human tumour cell lines were investigated for the first time. GC-FID and GC-MS analyses showed that trans-β-caryophyllene (30.9%), α-humulene (15.9%), α-copaene (7.8%), caryophyllene oxide (7.3%) and α-bisabolol (5.3%) are the major constituents of PM-EO. The antibacterial activity of PM-EO against a panel of oral patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…6 Essential oils extracted from Eugenia egensis DC., Eugenia flavescens DC., Eugenia patrisii Vahl, Eugenia polystachya Rich., Eugenia uniflora L., and Psidium myrtoides O. Berg showed cytotoxic activity against human cancer cell lines. 6,7 Myrtaceae are generally woody shrubs or tree species, mostly perennial, and commonly distributed in the tropics and subtropics. 8 Among the 132 Myrtaceae genera, Eugenia, Myrcia, and Psidium are the largest in the American and African continents, with more than 1400 occurring in different biomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Essential oils extracted from Eugenia egensis DC., Eugenia flavescens DC., Eugenia patrisii Vahl, Eugenia polystachya Rich., Eugenia uniflora L., and Psidium myrtoides O. Berg showed cytotoxic activity against human cancer cell lines. 6,7 Myrtaceae are generally woody shrubs or tree species, mostly perennial, and commonly distributed in the tropics and subtropics. 8 Among the 132 Myrtaceae genera, Eugenia, Myrcia, and Psidium are the largest in the American and African continents, with more than 1400 occurring in different biomes.…”
mentioning
confidence: 99%
“…6 Essential oils extracted from Eugenia egensis DC., Eugenia flavescens DC., Eugenia patrisii Vahl , Eugenia polystachya Rich., Eugenia uniflora L. , and Psidium myrtoides O. Berg showed cytotoxic activity against human cancer cell lines. 6,7…”
mentioning
confidence: 99%
“…The compound caryophyllene oxide was also dominant in the essential oil from P. cauliflora leaves (Apel et al, 2006). According to Yang et al (2000), caryophyllene oxide is utilized by the pharmaceutical, food and cosmetic industry as a preservative; besides that it is a significant compound in essential oil with antimicrobial activity (Dias et al, 2019), inhibiting action of acetylcholinesterase (Xiang et al, 2017) and antioxidant activity (Coté et al, 2017). The antioxidant action of caryophyllene oxide was evaluated from chemical compounds of the essential oil of Tanacetum vulgare L. α-pinene (IC50 of 3.4 µg/mL) and caryophyllene oxide (IC50 of 6.2 µg/mL) with antioxidant activity by DCFH-DA test (assay of dichloro-dihydro-fluorescein diacetate) in fibroblasts of human skin (Coté et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Medina et al (2011) showed that the araça (P. cattleianum Sabine) fruit extract presents total polyphenol concentrations up to 768 mg/100 g of fresh fruit pulp. Applications of Psidium species for medical purposes were also reported in the literature (Dias et al, 2018;Pereira et al, dos Pereira et al, 2018). Dias et al (2018) showed that P. myrtoides plant leaves are promising antibacterial and antitumor agents.…”
Section: Introductionmentioning
confidence: 92%
“…Applications of Psidium species for medical purposes were also reported in the literature (Dias et al, 2018;Pereira et al, dos Pereira et al, 2018). Dias et al (2018) showed that P. myrtoides plant leaves are promising antibacterial and antitumor agents. According to Pereira et al (dos Pereira et al, 2018), P. cattleianum Sabine fruits present potential application for prevention and treatment of pathologies associated to oxidative stress and aging, in addition to be used in the management of type 2 Diabetes mellitus.…”
Section: Introductionmentioning
confidence: 92%